2008
DOI: 10.1177/147323000803600508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Warming Devices for the Prevention of Core Hypothermia and Post-Anaesthesia Shivering

Abstract: The efficacy of forced air warming with a surgical access blanket in preventing a decrease in core temperature during anaesthesia and post-anaesthesia shivering (PAS) was compared with two widely used interventions comprising forced air warming combined with an upper body blanket, and a circulating water mattress, in a prospective, randomized double-blind study. A total of 90 patients undergoing total abdominal hysterectomy were studied, 30 in each group. Core temperature was measured 15, 30, 45, 60, 90 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
1
18
0
6
Order By: Relevance
“…This is particularly important for forced-air warming because air has a very low specific heat capacity. Increased coverage can explain the superior heat transfer ability of lower body blankets in comparison with smaller upper body blankets [64], and why surgical access blankets have significantly improved intra-operative temperature profiles when compared with upper body blankets [67].…”
Section: Types Of Forced-air Warming Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important for forced-air warming because air has a very low specific heat capacity. Increased coverage can explain the superior heat transfer ability of lower body blankets in comparison with smaller upper body blankets [64], and why surgical access blankets have significantly improved intra-operative temperature profiles when compared with upper body blankets [67].…”
Section: Types Of Forced-air Warming Systemsmentioning
confidence: 99%
“…Due to the greater specific heat capacity [108] and thermal conductivity [109] of water, it is, in theory, a more effective medium to transfer heat when compared with air. This theoretical advantage is not translated into a clinical one as all of the trials comparing the two different warming modalities favoured forced-air warming [53][54][55]67].…”
Section: Circulating Water Devicesmentioning
confidence: 99%
“…Systems vary in terms of whether heat is provided to the upper or lower body, full body or surgical site only (Motamed et al 2000, Ihn et al 2008, Insler et al 2008. Quieter convective warming systems (such as WarmAir Model 135Ô, Cincinnati Sub Zero, Cincinnati, OH, USA) have also recently been developed (Wagner et al 2008).…”
Section: Different Types Of Active Warming Systemsmentioning
confidence: 99%
“…Circulating-water mattress was compared with the forced-air warming system in four clinical trials (20)(21)(22)(23) .…”
Section: Comparison Between Circulating-water Mattress and The Forcedmentioning
confidence: 99%
“…The other three studies (20)(21)(22) reported that the forced-air warming system was better at preventing hypothermia (abdominal surgeries and general anesthetics). Three of the four clinical trials presented a Jadad score of 3 (moderate) (20)(21)(22) and one scored a 2 (low quality) (23) .…”
Section: Comparison Between Circulating-water Mattress and The Forcedmentioning
confidence: 99%